A Convergence Theorem of an Implicit Type Iteration in a Geodesic Space. (23rd May 2022) - Kimura, Yasunori; Torii, Kakeru
Abstract: In this paper, we define a quadrilateral inequality, Browder type and implicit iterative method in a CAT(1) space. Furthermore, we prove a convergence theorem of the implicit iterative method in the same space used the quadrilateral inequality.